Trade, conflicts, and political integration: the regional interplays - Vincent Vicard (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper investigates the determinants of the different forms taken by regional integration in different parts of the world. This raises the issue of the relationship between economic and political integration. The theoretical model shows that, in an insecure world, the interplays between security and economic forces shape the decision to form a regional trading agreement (RTA) and its institutional design. Empirical results confirm that regionalism should be understood as a regulation mechanism: countries experiencing more interstate disputes are more likely to create a deep RTA, such as custom union or common market, whereas international insecurity deters the formation of preferential and free trade agreements.
Keywords: D74; F02; F15; H56; 330